La sociedad salarial de servicios a debate: ciclo del capital, estructura social y subjetividad obrera - Albarracín Sánchez, Daniel (Cuadernos de Relaciones Laborales, 2003)
We propose to explore the characteristics and development of services societies, from a particular point of view: wage relations sociology. From a theoreticaly informed empirical work we analyse and bring some conclusions about the capitalist superindustrial society of services in a semiphery of Europe: Spain. We try to approach on the making of modern commodity and its shapes; an empirical study of occupational distribution of work-force in the Spanish capital cycle in the last 25 years; an analyse of classes structure and its evolution in Spain. We also approach to the making of subjectivity and identity of workers, in the framework of ‘wage relation experience’ reality, and contribute some elements to interpretate possible structurant changes in this country.